PENGARUH CURAH HUJAN PADA TEGANGAN BOLAKBALIK LEWAT DENYAR ISOLATOR GANTUNG KERAMIK - , SERTINO ANGGARA PUTRA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
High voltage system has been much developed, both from the magnitude of the applied voltage on the transmission and distribution of electric power as well as increased insulation used. Therefore it is needed an insulation system that ensures there is no direct contact between the poles of high voltage conductors. However, the reliability of an insulator that serves an insulation system can be reduced due to the influence of nature, especially the influence of rain that often happens in Indonesia. This study aimed to determine the effect of rainfall changes on flashover voltage of ceramic suspension insulator. This also compared the difference between flashover voltage in dry conditions and wet conditions. Testing is done by applying an alternating voltage (AC) to every one of the five insulators connected in series, the flashover voltage will be observed in dry conditions and wet conditions in accordance with the rainfal rate of Yogyakarta city. The results showed that the number of ceramic insulators connected in series affect the resistance of insulator when holding the flashover voltage, this also proved there is a difference of value between flashover voltage in dry conditions and wet conditions. With the increases of rainfall intensity, the value of flashover voltage in ceramic suspension insulator decreased. Amount of suspension insulator, the rainfall intensity, and the contaminants contained in the water can change the value of ceramic suspension insulator.